2013
DOI: 10.1371/journal.pone.0068763
|View full text |Cite
|
Sign up to set email alerts
|

A Pig Model of the Preterm Neonate: Anthropometric and Physiological Characteristics

Abstract: BackgroundLarge animal models are an essential tool in the development of rationally-based new clinical therapies for preterm infants. We provide a description of the newborn pig as a model of the preterm neonate in terms of growth parameters, physiology and the requirement for intensive care over a range of gestational ages.MethodsTwenty-nine litters of piglets (n = 298) were delivered by caesarean section at six timepoints during gestation from 91d to 113d (term = 115d). Two groups, at 91 and 97d gestation, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
87
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(90 citation statements)
references
References 36 publications
3
87
0
Order By: Relevance
“…The piglet model has been used in other studies on neonatal resuscitation [21]. Moreover, it has been suggested that newborn piglets can provide a relevant model for some aspects of human physiology during the neonatal period [24]. We did not use the Masimo Blue sensor which is intended for low oxygen saturation conditions [25].…”
Section: Discussionmentioning
confidence: 99%
“…The piglet model has been used in other studies on neonatal resuscitation [21]. Moreover, it has been suggested that newborn piglets can provide a relevant model for some aspects of human physiology during the neonatal period [24]. We did not use the Masimo Blue sensor which is intended for low oxygen saturation conditions [25].…”
Section: Discussionmentioning
confidence: 99%
“…However, the piglet model has been used in several studies on neonatal resuscitation [20,27]. Moreover, it has been suggested that newborn piglets can provide a relevant model of human preterm physiology during neonatal age [28]. We did not correct the CO-oximetry for porcine blood.…”
Section: Discussionmentioning
confidence: 99%
“…isoflurane anaesthesia (1-2% in air) for the duration of the surgery [23] . Upon delivery, the piglets were weighed and euthanised with an injection of sodium pentobarbital (325 mg/kg, intracardiac or umbilical artery).…”
Section: Animals and Tissue Preparationmentioning
confidence: 99%